2018
DOI: 10.3329/medtoday.v30i2.37810
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Serum Calcium Levels in Pre-eclampsia

Abstract: Pre-eclampsia is the most common medical complication of pregnancy associated with increased maternal and infant mortality and morbidity. Reduced serum calcium level are found associated with elevated blood pressure in preeclampsia. To evaluate serum calcium level in pre-eclamptic women. This cross sectional study was carried out in among 50 preeclamptic patients, aged 20 to 40 years, and gestational age ranges from 20 to 40 weeks and 50 age and gestational age matched normotensive pregnant women having no pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…Group II with p=0.619, it was in accordance with study done by Roy et al[17] which showed maternal mortality was 3.8% in patients with pregnancy-induced hypertension.…”
supporting
confidence: 89%
“…Group II with p=0.619, it was in accordance with study done by Roy et al[17] which showed maternal mortality was 3.8% in patients with pregnancy-induced hypertension.…”
supporting
confidence: 89%
“…A reduction in levels of nitric oxide mainly causes vasoconstriction and arterial stiffness. It is known that placental dysfunction is more likely to occur in PIH cases at less than 34 weeks of gestation [6,7], and early onset of PIH confers a substantially higher risk of thyroid, cardiovascular, respiratory, central nervous system, renal, and hepatic disorders [8,9]. However, in most previous studies, thyroid hormones were measured before 20 weeks of gestation.…”
mentioning
confidence: 99%